Methylation-based markers for the estimation of age in African cheetah, Acinonyx jubatus - (:unkn) unknown (My University, 2024)
Age is a key demographic in conservation where age classes show differences in important population metrics such as morbidity and mortality. Several traits, includingreproductive potential, also show senescence with ageing. Thus, the ability to estimateage of individuals in a population is critical in understanding the current structureas well as their future fitness. Many methods exist to determine age in wildlife,with most using morphological features that show inherent variability with age. Thesemethods require significant expertise and become less accurate in adult age classes,often the most critical groups to model. Molecular methods have been applied tomeasuring key population attributes, and more recently epigenetic attributes such asmethylation have been explored as biomarkers for age. There are, however, severalfactors such as permits, sample sovereignty, and costs that may preclude the use ofextant methods in a conservation context. This study explored the utility of measuringage-related changes in methylation in candidate genes using mass array technology. Novel methods are described for using gene orthologues to identify and assay regions for differential methylation. To illustrate the potential application, African cheetah was used as a case study. Correlation analyses identified six methylation sites with an age relationship, used to develop a model with sufficient predictive power for most conservation contexts. This model was more accurate than previous attempts using PCR and performed similarly to candidate gene studies in other mammal species. Mass array presents an accurate and cost-effective method for age estimation in wildlife of conservation concern.
Keywords: African Research